THE RELEVANCE OF AHMAD BAHAUDDIN NURSALIM'S THOUGHTS IN MODERNIZING ISLAMIC RELIGIOUS EDUCATION FOR THE MILLENNIAL GENERATION - Maghfiroh, Marjiatul; Mas'ud, Ali (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
Islamic education has an important role in forming individuals who are not only intellectually competent but also have good morals and a deep understanding of religion and apply it in their lives. There are several charismatic scholars who have recently gained popularity with their phenomenal thoughts on the concept of Islamic education, and one of them is Ahmad Bahauddin Nursalim. This research aims to describe the concept of Islamic education from Bahauddin Nursalim's perspective and its relevance to modernization. The research method used is descriptive-qualitative, with a library research type. Data was obtained through documentary techniques through online searches and using content analysis and hermeneutics. Ahmad Bahauddin Nursalim emphasized the concept of Islamic education, which is appropriate to the situation of this modern era, in several of his thoughts, which were grouped into three aspects of education, namely: aqidah, worship, and morals. According to him, the modernization of Islamic religious education must have the principle of integrating the treasures of classical knowledge with the development of modern technology, the center of which is love for Allah Swt.